THE EFFECT OF MOTIVATION, COMPENSATION AND CAREER DEVELOPMENT ON LECTURER PERFORMANCE AT SARI MUTIARA UNIVERSITY OF INDONESIA - Kalit, Desy R S; Simanjuntak, Markus Doddy; Barus, Alexander (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of motivation, compensation, and career development on lecturer performance at Sari Mutiara Indonesia University. The influence of motivation, compensation, and career development on lecturer performance at Sari Mutiara Indonesia University was analyzed partially and simultaneously. The research method used was quantitative descriptive research. Data collection used a questionnaire distributed directly to lecturers at Sari Mutiara Indonesia University using an online questionnaire in the form of a Google Form. The sample in this study was 65 lecturers at Sari Mutiara Indonesia University. The analytical methods used were validity testing, reliability testing, heteroscedasticity testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results showed that the variables of motivation (X1) and career development (X3) significantly affected lecturer performance (Y), while the variable of compensation had no effect. Therefore, it can be concluded that the influence of each variable partially, not all of them, but simultaneously influenced lecturer performance at Sari Mutiara Indonesia University. The data were processed statistically using SPSS 26